Improving Activity and Learning Outcomes of Sciences Using the “Peter Pan” Model in Elementary School Students - Prasetyarini, Try Ajeng; Aslamiah; Cinantya, Celia; Maimunah; Refia Refianti, Wahdah (Berpusi Publishing, 2023)
The backgrounds of this research are the low activity and learning outcomes in the science learning content of the fifth grade elementary school students. The solution used to overcome this problem is to use the